Desecration of Nanula Kue : impact of Taltson hydroelectric development on Dene Sonline - Bielawski, Ellen (Arctic Institute of North America, 1993)
The table of contents for this item can be shared with the requester. The requester may then choose one chapter, up to 10% of the item, as per the Fair Dealing provision of the Canadian Copyright Act